ANALISIS STRATEGI PENGEMBANGAN USAHA PADA UKM KAMIR DI KAMPUNG ARAB, KABUPATEN PEMALANG - Avi Puspita Desifrida; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2019)
Problem occurs in this research is because the stagnancy development of UKM Kamir in Arab Resident of Pemalang Regency. Because of less-trained profesionality and enterprenurship inside global competition, the Kamir entrepreneur need training about assets, human resource, technology and marketing. This research is made to explain: 1) asset’s view of development, 2) human resource’s view of development, 3) technology’s view of development and 4) marketing’s view of development. Using qualitative approaching with sentralized case study to Kamir entrepreneur in Arab Resident, using 6 (six) resource person by purposive sampling method. Researcher inner is coming in to deep questions and answers section with resource person to expound and explain about business development strategy of Kamir. The result is showing the average of assets development is on 11,67 (good). The average score of human resource is on 9,25 (average). Development from the technology used is sbout 11,00 (average). Kamir’s business development from marketing view is showed in 10,00 (average).